Critique of Social Conformity: Fall of the Feudal Order in B. P. Koirala’s Select Short Stories - Phuyal, Komal Prasad (Bagiswori Journal, 2025)
B. P. Koirala (1914-1982) examines the limits of social conformity in Nepal in the long 1930s and projects the fall of the feudal order, devoid of the issues of justice and social welfare. This paper reads “Doshi Chasma” [The Faulty Glasses], “Karnelko Ghoda” [The Colonel’s Horse], and “Madheshtira” [To the Madhesh] from the collection, Doshi Chasma [Faulty Glasses] (1949) in the historical context and examines the political purpose and goal for each of the major characters in the short fiction by applying the critical insights from Cultural Studies as furthered by During (2005), Storey (1997), and Hall (1997). Koirala develops tension from the interaction between the conformists and the nonconformists and aligns himself with the people from the bottom to defend them and critique the limits of the feudal order. The author looks into the spiritual emptiness of the Rana order, which torments and insults the people from the bottom to maintain the authority from the top. "Doshi Chasma" depicts an ordinary man, Keshav Raj, psychologically torturing himself after missing to greet the Rana General. Koirala critiques the impacts of the political order through the psychological upheavals in the protagonist. "Karnelko Ghoda" builds tension from the interaction between the conformist Colonel and the nonconformist bride. The author pictures the inner, empty self of the Colonel, who defeats himself by killing the horse. Finally, "Madheshtira” intertwines the conformist and the nonconformist self in the young widow who wants to live a settled life by finding a husband. She follows the codes of society as she believes in marriage as a way to a settled life. On the other hand, the widow also challenges the mores of society by deciding to marry again. This paper contextually reads Koirala’s selected stories to examine the limits of social conformity in the feudal order and explore its impact in shaping the course of each narrative.